Implications of the occlusal vertical dimension in the aesthetics of the facial lower third: a clinical study: The OVD in facial aesthetics - Vilardell, Judith; Martín Santiago, María del Pilar (Aesthetic Medicine, 2023)
Background and objective: An adequate occlusal vertical dimension (OVD) can decrease the fillers needed and better control of the volumes and symmetry, providing enhanced balance and better cosmetic results to the human face. The study’s objective was to show how an increase or decrease in the ideal measurement of the occlusal vertical dimension affects the aesthetics of the lower facial third and how restoring it through oral rehabilitation prior to facial aesthetic treatments helps optimize cosmetic results. Methods: This was a single-center, comparative, non-randomized study including soft profile measurements using teleradiography to verify whether aesthetic standards were met before and after prosthetic rehabilitation, with other assessments based on frontal images of the patient’s face. The need to decrease fillers was assessed through the photographs obtained and with the patient’s input. A golden section gauge and an electronic vernier caliper were used to check the presence of a golden proportion before and after oral rehabilitation and restore the ideal occlusal vertical dimension. Results: The study enrolled 12 patients, divided into three age groups (Group 1: 41−50 years old; Group 2; 51−60 years and Group 3: 61−70 years old), with a mean sample age of 57.25 years (SD 9.85). A direct relationship was found between the occlusal vertical dimension and orofacial aesthetics, so an early intervention in the intraoral treatment optimized the subsequent facial treatment. Conclusions: Achieving optimal intraoral volume helps improve asymmetries resulting from edentulism while improving the vertical dimension of the lower third, in turn improving extraoral and facial patient management, minimizing the number of fillers, and avoiding more invasive surgical facial treatments. The study results highlighted the importance of establishing collaboration between dentists and aesthetic medicine specialists.